Targeting SARS‐CoV‐2 Spike Protein/ACE2 Protein‐Protein Interactions: a Computational Study. Issue 6 (27th April 2021) - Pirolli, Davide; Righino, Benedetta; De Rosa, Maria Cristina
Abstract: The spike glycoprotein (S) of the SARS‐CoV‐2 virus surface plays a key role in receptor binding and virus entry. The S protein uses the angiotensin converting enzyme (ACE2) for entry into the host cell and binding to ACE2 occurs at the receptor binding domain (RBD) of the S protein. Therefore, the protein‐protein interactions (PPIs) between the SARS‐CoV‐2 RBD and human ACE2, could be attractive therapeutic targets for drug discovery approaches designed to inhibit the entry of SARS‐CoV‐2 into the host cells. Herein, with the support of machine learning approaches, we report structure‐based virtual screening as an effective strategy to discover PPIs inhibitors from ZINC database. The proposed computational protocol led to the identification of a promising scaffold which was selected for subsequent binding mode analysis and that can represent a useful starting point for the development of new treatments of the SARS‐CoV‐2 infection. Abstract :